THE NECESSITY OF SMART TECHNOLOGIES IN THE TRAINING OF FUTURE PRIMARY SCHOOL TEACHERS IN THE MODERN ERA (International Conference on Educational Discoveries and Humanities, 2025)
In an age where knowledge flows faster than rivers in spring, teacher education cannot remain anchored in yesterday. This study examines the essential role of smart technologies in preparing future primary school teachers, highlighting how digital tools enhance pedagogical readiness, cognitive flexibility, and classroom innovation. The analysis reveals that smart devices, cloud platforms, AI-assisted learning systems, and multimodal digital resources create a multisensory environment that aligns with children’s developmental needs. These technologies not only modernize instructional approaches but also cultivate reflective, data-literate, and creatively empowered teachers. The research concludes that smart technologies are no longer optional; they are the pulse of contemporary teacher preparation.